Orthodontic treatment of a case with a congenitally missing maxillary canine and a malformed contralateral canine - Masoud Ahmed I.; Bindagji Feras H. (Sciendo, 2021)
Excluding third molars, the prevalence of tooth agenesis of permanent teeth ranges from 1.6% to 9.6%. The congenital absence of maxillary permanent canines is a rare condition with a reported prevalence of less than 0.5%. Case reports describing congenitally missing permanent canines are uncommon, and those that involve treatment are even more rare.